2017
DOI: 10.22410/issn.2176-3070.v9i3a2017.1328
|View full text |Cite
|
Sign up to set email alerts
|

O Ambiente De Cuidado Em Uti Neonatal: A Percepção Dos Pais E Da Equipe De Saúde

Abstract: Resumo: O estudo objetivou conhecer a percepção de pais e equipe de saúde sobre o cuidado prestado à criança internada em uma Unidade de Terapia Intensiva Neonatal (UTIN) de um hospital de médio porte localizado no interior do Rio Grande do Sul. A pesquisa foi descritiva e exploratória, com abordagem qualitativa. Os informantes da pesquisa foram nove pais de recém-nascidos internados em uma UTIN e 19 profissionais de saúde desta unidade, estes foram entrevistados e realizado análise de conteúdo temática segund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…There is limited data in Brazil regarding neonatal pain and the knowledge of the physiotherapist. In addition, the studies found do not individualize this professional category and therefore have a low number of physiotherapists, with emphasis on the team as a whole [17][18][19] . It is possible to see that professionals from other areas caring for newborns in the neonatal ICU also do not have the specific knowledge regarding pain care and that there are discrepancies between clinical practice and perception regarding the presence or absence of painful stimulus 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data in Brazil regarding neonatal pain and the knowledge of the physiotherapist. In addition, the studies found do not individualize this professional category and therefore have a low number of physiotherapists, with emphasis on the team as a whole [17][18][19] . It is possible to see that professionals from other areas caring for newborns in the neonatal ICU also do not have the specific knowledge regarding pain care and that there are discrepancies between clinical practice and perception regarding the presence or absence of painful stimulus 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Uma vez que, o nascimento de uma criança é um processo transformador dentro da família (Lucas et Al., 2009). Em recém-nascidos que necessitam de UTI logo após o nascimento, essa primeira vivência é quebrada, devido o momento, onde este necessita de dispositivos e equipamentos, necessários a manutenção de sua vida (Lohmann, 2011).…”
Section: Introductionunclassified